Words of the Wise Are like Goads: Engaging Qohelet in the 21st Century - Boda, Mark J. (Eisenbrauns, 2014)
Intro -- Contents -- Preface -- Part 1 -- Early History of Interpretation -- Ecclesiastes in Premodern Reading: Before 1500 c.e. -- Eric S. Christianson -- Qohelet and the Rabbis -- Ruth Sandberg -- Ecclesiastes and the Reformers -- Al Wolters -- Sweet and Lawful Delights: Puritan Interpretations of Ecclesiastes -- Cristian G. Rata -- Part 2 -- History, Form, and Rhetoric -- Determining the Historical Context of Ecclesiastes -- Tremper Longman III -- The Book of Qohelet "Has the Smell of the Tomb about It": Mortality in Qohelet and Hellenistic Skepticism -- Leo G. Perdue -- Qohelet and Royal Autobiography -- Martin A. Shields -- Framed! Structure in Ecclesiastes -- David J. H. Beldman -- The Poetry of Qohelet -- John F. Hobbins -- Part 3 -- Key Concepts and Passages -- Epistemology in Ecclesiastes: Remembering What It Means to Be Human -- Ryan P. O'Dowd -- "Riddled with Ambiguity": Ecclesiastes 7:23-8:1 as an Example -- Doug Ingram -- The Meaning of הבל in Qohelet: An Intertextual Suggestion -- Russell L. Meek -- Speaking into the Silence: The Epilogue of Ecclesiastes -- Mark J. Boda -- Part 4 -- Language and Grammar -- The Grammar of - and א ר in Qohelet -- Robert Holmstedt -- The Verb in Qohelet -- John Cook -- "Aramaisms" in Qohelet: Methodological Problems in Identification and Interpretation -- Eva Mroczek -- Part 5 -- Interpreting Qohelet -- The Theology of Ecclesiastes -- Craig G. Bartholomew -- Ecclesiastes and the Canon -- Stephen G. Dempster -- Fresh Perspectives on Ecclesiastes: "Qohelet for Today" -- Iain Provan -- Preaching Qohelet -- Daniel C. Fredericks -- Solomon's Sexual Wisdom: Qohelet and the Song of Songs in the Postmodern Condition -- Peter J. Leithart -- Works Cited -- Index of Authors -- Index of Scripture -- Index of Other Ancient Sources.